Analysis of changes in bread during frozen storage with pre-cooking and steaming - Siti Nur Azizah; Wisnu Adi Yulianto; Ch. Lilis Suryani (LPPMPK- Universitas Muhammadiyah Cileungsi, 2024)
Frozen storage methods in bakery products have been widely applied to maintain quality and extend shelf life. Early cooking by steaming followed by frozen storage on bread is an effective way to slow down the spoilage process. The length of time frozen storage affects the physical, chemical, microstructure, thermal, and sensory reception properties. The purpose of this study is to evaluate the quality of bread by pre-cooking steaming during frozen storage and after re-cooking. The research was carried out with the storage time treatment factors, time of 0, 14, 28, 42, 56 and 70. Parameters analyzed in frozen bread include texture testing, volume expansion rate, moisture content, dissolved protein content and crumbs (SEM), thermal properties with Differential Scanning Calorimatry, as well as the level of preference. The result showed that the longer the frozen storage, the harder the texture, the level of volume development, the lower the water and dissolved protein content and the smaller the pores of the bread. Bread texture increased in hardness along with the lenght of frozen storage, namely 8.70 N increased to 17.44 N, while the water content decreased from 30.02% (w/w) to 26.70% (w/w). the highest soluble protein content was obtained on the 14th day which was 1.53% and the lowest was on the 70th day, which was 1.31%. The result of the SEM test showed that there was a reduction in the pore size of bread compared to on day 0. The results of DSC thermogram showed that the longer the frozen storage of bread with the initial cooking of steaming, the lower the gelatinization and enthalpy temperatures, and the smaller the pore size is small. Storage of frozen bread until day 56 resulted in bread quality that has nor changed and is still accepted by the panelists.